Effect of Sr substitution on structure and thermal diffusivity of Ba1-xSrxTiO3 ceramic - Ridha, Noor Jawad; Mat Yunus, Wan Mahmood; Shaari, Abdul Halim; Talib, Zainal Abidin; Al-Asfoor, Firas Kamel Mohamad; Primus, Walter Charles (Science Publications, 2009)
Problem statement: The aim of this research was to study the effect of Sr substitution on structure and thermal diffusivity of Bal-xSrxTiO3 ceramic at room temperature. Approach: Structural and thermal diffusivity of Ba1-xSrxTiO3 were studied by performing X-ray diffraction and photoflash measurements. The effects of Sr substitution on the structure and on the thermal diffusivity of Ba1-xSrxTiO3 (0≤x≤1) were investigated. All samples were prepared by standard solid state reaction technique. Results: The results showed that by substituting of Ba2+ ion with the Sr2+ the crystallite size decreased. The effect made the thermal diffusivity of Ba1-xSrxTiO3 decreased from 11.30x10-3 cm2 sec-1 (for BaTiO3) to 6.467x10-3 cm2 sec-1 (for SrTiO3) as x varied from 0-1. Conclusion: This study showed a significant effect of structure on thermo-physical property of materials.